2016
DOI: 10.1515/aut-2016-0037
|View full text |Cite
|
Sign up to set email alerts
|

Fabric Selection for the Reference Clothing Destined for Ergonomics Test of Protective Clothing: Physiological Comfort Point of View

Abstract: The currently used methods of ergonomic assessment of protective clothing depend on the subjective feeling of research participants and don’t take into consideration all aspects of its use. Therefore, more amount of work is undertaken toward the development of new research tools for the ergonomic assessment of protective clothing. Research was carried out at the Central Institute for Labour Protection – National Research Institute in Lodz. A new methodology will take into consideration a variant of reference c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 15 publications
(17 reference statements)
0
2
0
Order By: Relevance
“…It is proved that thermal properties are hardly affected by the capillary structure of fibres and yarn surface geometry. Also, air in the knitted fabric structure plays a prevalent role in heat transfer [108,112]. Air permeability may be defined as a function of the loop density, tightness and thickness whilst water vapour permeability greatly depends on the material properties [113].…”
Section: Additional Functionality Of Medical Compression Garmentsmentioning
confidence: 99%
“…It is proved that thermal properties are hardly affected by the capillary structure of fibres and yarn surface geometry. Also, air in the knitted fabric structure plays a prevalent role in heat transfer [108,112]. Air permeability may be defined as a function of the loop density, tightness and thickness whilst water vapour permeability greatly depends on the material properties [113].…”
Section: Additional Functionality Of Medical Compression Garmentsmentioning
confidence: 99%
“…The Technical Requirements for Medical Disposable Protection numbered GB19082-2009 has stipulated that the humidity permeability of MDPC should not be less than 2500 [7] . Bartkowiak et al [13] put forward the viewpoint of sensory comfort by choosing the fabric of reference clothing for ergonomics test of MDPC. Jiang et al [14] conducted a humidity permeability test on the comfort of several different MDPC fabrics, the research showed that the humidity permeability of various coated materials was far lower than that level.…”
Section: Introductionmentioning
confidence: 99%
“…The Technical Requirements for Medical Disposable Protection numbered GB19082-2009 has stipulated that the humidity permeability of MDPC should not be less than 2500 g/(m2 d) [7]. Bartkowiak et al [13] put forward the viewpoint of sensory comfort by choosing the fabric of reference clothing for ergonomics test of MDPC. Jiang et al [14] conducted a humidity permeability test on the comfort of several different MDPC fabrics, the research showed that the humidity permeability of various coated materials was far lower than that level.…”
Section: Introductionmentioning
confidence: 99%